The Role Of Microfinance In Poverty Reduction: Countries Experiences by Regions 2000-2018 - El-Nasharty, Heba (Innovation Journal of Social Sciences and Economic Review, 2022)
The purpose of this study is to evaluate the impact of microfinance provisions on poverty reduction across various developing and a few developed countries, examining how regional differences and time influence the performance of the microfinance industry. The study employs a panel data model and pooled Ordinary Least Squares (OLS) to analyze the effect of key microfinance indicators—namely, the number of microfinance institutions, gross loan portfolio, and microfinance intensity (gross loan as a percentage of GDP)—in conjunction with control variables such as inflation, employment, population growth, trade openness, and the contributions of agriculture and industry to GDP. The empirical analysis is conducted using panel data from 91 countries across six regions, covering the period from 2000 to 2018, with data sourced from the World Development Indicators and the Microfinance Information Exchange (MIX) Market. The findings of the study indicate that microfinance indicators significantly reduce poverty, highlighting the critical role of microfinance in improving the living standards of disadvantaged populations. Additionally, the study finds that certain control variables also contribute to poverty reduction, further supporting the efficacy of targeted economic policies. This study underscores the importance of microfinance as a tool for poverty alleviation, particularly in regions with high poverty rates and low financial inclusion. The research also suggests that enhancing the performance of the microfinance sector can aid governments in achieving their poverty reduction goals. The implications of this study are significant for policymakers and stakeholders in the microfinance industry. It calls for the development of regulatory frameworks, legislative reforms, and policies aimed at strengthening the microfinance sector. Moreover, the study highlights the need for continuous training, capacity building, and support to ensure the sustainability and effectiveness of microfinance initiatives.
Keywords: Poverty; Microfinance; Financial Sector; Employment; Egypt